JUSTICE AND ITS ADMINISTRATION IN IGBOLAND BEFORE THE DAWN OF THE PRESENT MILLENNIUM - Rex, Obiwuru Chidera (Journal of Historical Studies, 2020)
Justice, one of the requisites for a healthy society, is not novel in Igbo land. Its presence in Igbo land prior to the 2000s is undeniable. Put differently, there has been administration of justice virtually in all facets of life in Igbo society even before the white man's "Santa Marias" and conveyances landed on the shores and borders of Eastern Nigeria. Igbo maxims such as onye ruo, o rie (idlers should know no pay/no work, no pay); egbe bere, ugo bere; nke siri ibe ya ebena nku kwaya (let the affluent as well as the indigent live; but let any between them that opposes the other's existence be the first to be ostracized/exited); ochu nwa okuko nwe ada; nwa okuko nwe oso (he who tries to harm the innocent must end up harming himself); ihe onye metara, o buru (whatsoever one's actions are, one must face the consequences); e mere nwata ka emere ibe ya, obi adi ya nma (all should be treated equally for peace's sake), etc. abound. Be that as it may, this paper seeks to painstakingly look at justice from the set of Igbo binoculars; that is, how it was perceived by and its importance to the Igbo people. It also scrutinized the various institutions responsible for and aid in the administration of justice in Igbo society before now. All in all, some negative changes that have occurred in the Igbo society in the present millennium in respect to administration of justice is not left unconsidered.